2017
DOI: 10.1371/journal.pone.0180517
|View full text |Cite
|
Sign up to set email alerts
|

Tales of diversity: Genomic and morphological characteristics of forty-six Arthrobacter phages

Abstract: The vast bacteriophage population harbors an immense reservoir of genetic information. Almost 2000 phage genomes have been sequenced from phages infecting hosts in the phylum Actinobacteria, and analysis of these genomes reveals substantial diversity, pervasive mosaicism, and novel mechanisms for phage replication and lysogeny. Here, we describe the isolation and genomic characterization of 46 phages from environmental samples at various geographic locations in the U.S. infecting a single Arthrobacter sp. stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(80 citation statements)
references
References 53 publications
5
72
1
Order By: Relevance
“…Transmission electron microscopy (TEM) at 67,000X magnification showed an average phage capsid diameter and tail length of 48 ± 8 nm and 156 ± 53 nm, respectively (Fig 1b). The long, flexible, non-contractile tail suggested BlueFeather's classification as a Siphoviridae (Yuan and Gao 2017 (Klyczek et al 2017). The average Arthobacter phage genome length (as of May 2020) was 46,968 bp with a standard deviation of 20,619 bp and a median length of 53,859 bp, suggesting that most Arthrobacter phages have genomes notably larger than that of BlueFeather.…”
Section: Bluefeather Is a Siphovirus With A Short Genomementioning
confidence: 99%
See 2 more Smart Citations
“…Transmission electron microscopy (TEM) at 67,000X magnification showed an average phage capsid diameter and tail length of 48 ± 8 nm and 156 ± 53 nm, respectively (Fig 1b). The long, flexible, non-contractile tail suggested BlueFeather's classification as a Siphoviridae (Yuan and Gao 2017 (Klyczek et al 2017). The average Arthobacter phage genome length (as of May 2020) was 46,968 bp with a standard deviation of 20,619 bp and a median length of 53,859 bp, suggesting that most Arthrobacter phages have genomes notably larger than that of BlueFeather.…”
Section: Bluefeather Is a Siphovirus With A Short Genomementioning
confidence: 99%
“…Previous research on mycobacteriophages concluded that phages may exhibit a continuum of diversity, wherein genes are constantly being shuffled amongst the phage population, resulting in shared genes and sequences between different clusters (Pope et al 2015). The immense and ever-expanding diversity of phage genomes has historically been categorized in terms of nucleotide sequence conservation, with a minimum 50% nucleotide identity and 50% span length to at least one phage in a cluster to warrant membership (Hatfull et al 2010;Klyczek et al 2017). A mass scale study on Gordonia phages also identified a spectrum of genetic diversity, as clusters did not have clear boundaries (Pope et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because such a large number have been morphologically examined, it seems unlikely that mycobacteriophages with podoviral morphologies exist. Interestingly, phages with podoviral morphologies have been described for other actinobacterial hosts, including Arthrobacter and Streptomyces (37, 38), suggesting that the absence of podoviral mycobacteriophages is due to a physical blockage presented by mycobacterial cell walls, rather than being evolutionarily inaccessible.…”
Section: General Mycobacteriophage Featuresmentioning
confidence: 99%
“…Cluster F and Cluster J), where they are present in addition to their canonical repressors. For example, Fruitloop (Cluster F1) has a canonical repressor (gene 44 ) which confers immunity to itself and some other Cluster F1 phages, and the stolen repressor (37) which shares 97% amino acid identity with the Bxb1 repressor. Fruitloop gene 37 is expressed in a lysogen, although at a somewhat lower level than the canonical repressor (62), but confers immunity to at least some Cluster A1 phages such as SkiPole and Pinto (unpublished observations).…”
Section: Drivers Of Mycobacterial and Mycobacteriophage Dynamicsmentioning
confidence: 99%